Investigating the interplay between formal and informal leaders in a shared leadership configuration: A multimodal conversation analytical study - Van De Mieroop, Dorien; Clifton, Jonathan; Verhelst, Avril (Human relations (New York), 2020)
Leader identity has traditionally been associated with hierarchical position (formal leadership). Yet, while there is an increasing tendency to regard leadership as a collective and distributed process, very little is known about the interplay of formal and informal leadership as in situ social practice within a hierarchical context. Using video-recordings of naturally occurring workplace interaction as data and arguing that insights from applied linguistics can be profitably employed to address such a lacuna, we use multimodal conversation analysis (CA) to show how ‘doing’ leadership is not limited to the formal leader. Rather, through talk, gaze, the use of space, artefacts and so on, it is negotiated in subtle ways which allow informal leadership to emerge in conjunction, and in this case in conflict, with formal leadership. We conclude this article by discussing the wider implications of these findings to both leadership theory and methodologies used to investigate the ‘just whatness’ of leadership.